O direito do trabalho como sistema imunológico da sociedade - Supioni, Adriana Jardim Alexandre (2019)
The present thesis establishes the immunological function of Labor Law in relation to the social conflict emanating from de relations between capital and labor. The analysis was based on the Social Systems Theory developed by Niklas Luhmann. The choice was made because it is compatible with the complexity of today´s society and the social systems that operate in it. Research is about interaction of the legal, political and economic functional systems and their effects on Labor Law. The proposal is to identify the role of Labor law in supplying the social system with an immunological force, not absolute, but important, to contain, or at least minimize the conflict arising from labor relations